PENGARUH PEMBERIAN PENYULUHAN PERILAKU HIDUP BERSIH SEHAT (PHBS) TENTANG TEKNIK MENCUCI TANGAN TERHADAP PENGETAHUAN MENCUCI TANGAN DI SD N 55 BATANG PIARAU LUBUK BASUNG KABUPATEN AGAM TAHUN 2014 - Junios, Junios; Rina, Rina (LPPM Universitas Prima Nusantara Bukittinggi, 2014)
Handwashing behavior was not a usual day-to-day by the general public. Hand washing is an important thing to know melai children from an early age in order to materialize a clean and healthy lifestyle. Namunberdasarkan data that has been collected from SDN 55 Batang piarau, still a lack of knowledge of the student / i for washing hands. The purpose of this study was to determine the effect of granting extension Net sehah Behavior (PHBs) About Handwashing Handwashing Against knowledge in SD N 55 Rods Piarau Lubuk Basung Agam 2015.This study design using pre-Eksprimental One group pre-post test desaign. This research was conducted at SDN 55 Batang piarau 03 September to 7 September 2015. The population in this study were 55 students / I with a total sample of 47 students / i. The data in this study was collected using questionnaires and processed by paired t-test.Based on the analysis of the data showed that respondents' knowledge before the intervention is given 100% low knowledge, and after being given the intervention of knowledge increased to 70.2% of respondents berpengrtahuan high, 23.4% of respondents were knowledgeable and 6.3 berpengetahuanrendah respondents about hand washing. Statistically, the provision of information has a significant influence in increasing student knowledge / i (p = 0.000)Recommended to students / I that higher knowledge in order to maintain and improve health with a clean and healthy life behavior, and student / i knowledgeable Low harder to improve his knowledge in order to create a clean and healthy lifestyle. For a school to reactivate UKS.